Countering Hoarding: A Sharia Microeconomic Literature Review on National Food Distribution Disparities amid Inflation - Jamila, Khaidar rahmaini; Ridwan, Muhammad; Soemitra, Andri; Yusrizal (International Journal of Economics, Science, and Education, 2025)
ABSTRACT Purpose: This study examines the role of hoarding (iḥtikār) and food distribution inequality in driving food inflation in Indonesia from the perspective of Islamic microeconomics. Design/methodology/approach: A qualitative approach is employed through a systematic literature review of classical fiqh sources, contemporary Islamic economic theory, national macroeconomic data, and policy-related reports. Findings: The study finds that hoarding contributes directly to food inflation, social welfare deterioration, and distributive injustice. Islamic economic principles prohibit such practices due to their inconsistency with distributive justice (‘adl), public welfare (maṣlaḥah), and the objectives of Sharīʿah (maqāṣid al-sharīʿah). Research limitations/implications: The study is limited to secondary data and conceptual analysis without empirical field investigation. Practical implications: State intervention, price controls, and Sharīʿah-based redistributive instruments such as zakat and infaq are justified to correct market failures. Originality/value: This paper integrates Islamic microeconomic principles into contemporary food inflation discourse. Paper type: Literature review Keywords: distributive justice, food distribution, hoarding, inflation, iḥtikār, Islamic microeconomics